Recent advances in paediatric cardiac anaesthesia - Vakamudi, Mahesh (Medknow Publications & Media Pvt Ltd, 2012)
Paediatric cardiac anaesthesia involves anaesthetizing very small children with complex congenital heart disease for major surgical procedures. The unique nature of this patient population requires considerable expertise and in-depth knowledge of the altered physiology. There have been several developments in the last decade in this subspecialty that has contributed to better care and improved outcome in this vulnerable group of patients. The purpose of this review is to present some of the recent advances in the anesthetic management of these children from preoperative evaluation to postoperative care. This article reviews the role of magnetic resonance imaging and contrast-enhanced magnetic resonance angiography in preoperative evaluation, the use of ultrasound to secure vascular access, the use of cuffed endotracheal tubes, the optimal haematocrit and the role of blood products, including the use of recombinant factor VIIa. It also deals with the advances in technology that have led to improved monitoring, the newer developments in cardiopulmonary bypass, the use of centrifugal pumps and extracorporeal membrane oxygenation and the role of DHCA. The role of new drugs, especially the α-2 agonists in paediatric cardiac anesthetic practice, fast tracking and effective postoperative pain management have also been reviewed.